2015
DOI: 10.1038/srep14909
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Activation is Mediated via a Functional Switch of the Rpt6 C-terminal Tail Following Chaperone-dependent Assembly

Abstract: In the proteasome, the proteolytic 20S core particle (CP) associates with the 19S regulatory particle (RP) to degrade polyubiquitinated proteins. Six ATPases (Rpt1-Rpt6) of the RP form a hexameric Rpt ring and interact with the heptameric α ring (α1–α7) of the CP via the Rpt C-terminal tails individually binding to the α subunits. Importantly, the Rpt6 tail has been suggested to be crucial for RP assembly. Here, we show that the interaction of the CP and Rpt6 tail promotes a CP-Rpt3 tail interaction, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…When the free base docks onto the CP, the C-terminal tail of Rpt6 appears to bind to the pocket between the CP α2 and α3 subunits, while Nas6 remains bound to Rpt3. This Rpt6 binding to the CP may then promote the release of Nas6[122]. Specifically, Rpt6 tail-CP binding is thought to promote Rpt3 tail insertion into a CP α-ring pocket, causing a steric clash between Nas6 and the CP and Nas6 dissociation[122].…”
Section: The Rp Basementioning
confidence: 99%
See 1 more Smart Citation
“…When the free base docks onto the CP, the C-terminal tail of Rpt6 appears to bind to the pocket between the CP α2 and α3 subunits, while Nas6 remains bound to Rpt3. This Rpt6 binding to the CP may then promote the release of Nas6[122]. Specifically, Rpt6 tail-CP binding is thought to promote Rpt3 tail insertion into a CP α-ring pocket, causing a steric clash between Nas6 and the CP and Nas6 dissociation[122].…”
Section: The Rp Basementioning
confidence: 99%
“…This Rpt6 binding to the CP may then promote the release of Nas6[122]. Specifically, Rpt6 tail-CP binding is thought to promote Rpt3 tail insertion into a CP α-ring pocket, causing a steric clash between Nas6 and the CP and Nas6 dissociation[122]. A recent report showed that Nas6 also prevents association of the base and lid, but specifically when ATP hydrolysis is inhibited, suggesting a switch in Nas6 positioning that may coordinate proper assembly of the full 26S proteasome[116].…”
Section: The Rp Basementioning
confidence: 99%
“…In yeast proteasomes, three of the six Rpt tails contain recognizable HbYX motifs, and these tails insert into specific α pockets in the holoenzyme (8, 9, 35, 36) (Figure 1C–D). However, significant evolutionary conservation is evident in the other tails, so they may also insert into α pockets conditionally or have a related function in the complex (37, 38). In any case, these tail-pocket interactions are the major, though probably not sole (35), means by which the RP and CP are joined.…”
Section: The Atpase Ring Of the Regulatory Particlementioning
confidence: 99%
“…Tian et al reported that the CP exhibits unexpected asymmetry, in that one side of the ring makes 1:1 contacts between Rpt2 and α4, Rpt6 and α3, and Rpt3 and α2, whereas on the opposite side, the tails of Rpt1, Rpt4 and Rpt5 cross-link with α5/α6, α7/α1, and α6/α7, respectively (38). The Rpt6-α3 interaction promotes both the Rpt3-α2 interaction through ATP-dependent binding with Nas6 and the release of Nas6 from the proteasome (39). Both Ecm29 and Hsp90 have been shown to regulate RP-CP assembly.…”
Section: Regulation and Underlying Molecular Mechanisms Of Proteasomementioning
confidence: 99%